Contemporary Views on Common Risk Factors and Pathophysiological Mechanisms of Acid-Related Gastrointestinal Disorders and Ischemic Heart Disease - Ortiq o’g’li, Raupov Abdurahmon (Journal of Innovation in Education and Social Research, 2025)
The comorbidity of ischemic heart disease and acid-related gastrointestinal illnesses is examined in this review, with an emphasis on common risk factors and pathophysiology connections. It draws attention to the part that pharmaceutical interactions, metabolic imbalance, and systemic inflammation play in the development of illness. The results provide insights for better clinical management of comorbid illnesses and are based on meta-analyses and extensive investigations.